2010
DOI: 10.1079/pavsnnr20105030
|View full text |Cite
|
Sign up to set email alerts
|

Poultry sector development, highly pathogenic avian influenza and the smallholder production systems.

Abstract: Poultry sectors are the fastest-changing component of the general livestock sector. These changes are typified by tremendous growth in poultry populations in industrial production systems. These industrial systems generally separate feed mills, breeding, production and processing into different operations. In a competitive market environment, such operations may be physically separated, but are closely integrated by strong private regulations. In less competitive market environments, encouraged by protection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the contrary, sanitary risk management was best addressed by the large companies’ set of sanitary rules and inspection processes (HACPP and ISO systems, production standards through farming contracts). Other studies demonstrated the parallel between a higher level of governance structure or formal arrangements, and enhanced biosecurity ( Okello et al, 2010 , Rushton, 2010 ). This raises the concern of higher prices for safer food and questionable accessibility of quality products for the majority of the Nairobi’s population living in informal settlements ( APHRC, 2014 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the contrary, sanitary risk management was best addressed by the large companies’ set of sanitary rules and inspection processes (HACPP and ISO systems, production standards through farming contracts). Other studies demonstrated the parallel between a higher level of governance structure or formal arrangements, and enhanced biosecurity ( Okello et al, 2010 , Rushton, 2010 ). This raises the concern of higher prices for safer food and questionable accessibility of quality products for the majority of the Nairobi’s population living in informal settlements ( APHRC, 2014 ).…”
Section: Discussionmentioning
confidence: 95%
“…Unlike farmers, traders in both markets studied had formed an association, in hope to improve their negotiation power with the Council. This initiative raises the question of government involvement versus private implementation of sanitary safeguards, which has the potential to translate into higher biosecurity ( Rushton, 2010 ). In a setting where corruption issues have been reported by participants, and hinder the fulfilling of some official sanitary roles, the potential benefits of private initiatives for the industry call for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…As international organizations such as FAO (Devendra 1993, Grimes 2002, Leibler, Otte et al 2009, Ozawa 1993, Ramaswamy 1985, Rushton, Viscarra et al 2011, Speedy 2003, USAID , the International Atomic Energy Agency (IAEA) (Ramaswamy 1985), the World Organization for Animal Health (OIE) (Cocks, Robertson et al 2012, Edwards 2003, Wijaszka 2010, Wongsathapornchai, Salman et al 2008, the Australian Centre for International Agriculture…”
Section: Livestock Disease Control Infrastructure In Myanmarmentioning
confidence: 99%
“…As the demand for meat continues to grow in South Asia and Africa and access to communal sources of water and forage shrinks, intensification of small-scale livestock systems in peri-urban areas is expected to expand (FAO, 2010). In South East Asia, smallholder transition to livestock intensification has been transformative, increasing economic opportunities while also introducing new disease risks and increasing demand on limited resources (Rushton et al , 2010).…”
Section: Introductionmentioning
confidence: 99%